2015
DOI: 10.1038/ncomms7285
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of STAT3 signalling promotes KRAS-induced lung tumorigenesis

Abstract: STAT3 is considered to play an oncogenic role in several malignancies including lung cancer; consequently, targeting STAT3 is currently proposed as therapeutic intervention. Here we demonstrate that STAT3 plays an unexpected tumour-suppressive role in KRAS mutant lung adenocarcinoma (AC). Indeed, lung tissue-specific inactivation of Stat3 in mice results in increased KrasG12D-driven AC initiation and malignant progression leading to markedly reduced survival. Knockdown of STAT3 in xenografted human AC cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
115
4
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(135 citation statements)
references
References 68 publications
13
115
4
3
Order By: Relevance
“…Similarly, IL-6 and STAT3 are usually considered oncogenic proteins 24,44 but they have tumor suppressor properties in some contexts. 45 Consistent with this idea, short-term engraftment of CLL cells was enhanced by IL-6 in the absence of exogenous TLR signaling ( Figure 4B), suggesting a tumorpromoting effect of IL-6 in this model. However, TLR7 and TLR9 signaling are involved in the pathogenesis of progressive CLL.…”
Section: Discussionsupporting
confidence: 72%
“…Similarly, IL-6 and STAT3 are usually considered oncogenic proteins 24,44 but they have tumor suppressor properties in some contexts. 45 Consistent with this idea, short-term engraftment of CLL cells was enhanced by IL-6 in the absence of exogenous TLR signaling ( Figure 4B), suggesting a tumorpromoting effect of IL-6 in this model. However, TLR7 and TLR9 signaling are involved in the pathogenesis of progressive CLL.…”
Section: Discussionsupporting
confidence: 72%
“…6C). It has been shown that oncogenic KRAS-driven cancers require TBK1, which regulates BCL-XL expression (30) and cell survival involving autocrine IL-6, CCL5, and STAT3 signaling (31). In KRAS mutant HCT116 cells, however, we found that suppression of TBK1 by shRNA did not attenuate BCL-XL protein levels (Fig.…”
Section: Stat3 Regulates Bcl-xl Induction In Kras Mutant Cells-contrasting
confidence: 49%
“…1A; refs. 7,40). By contrast, extensive AAH, diffuse AIS, and areas of invasive adenocarcinoma were observed throughout the lungs of gp130 F/F :Kras G12D mice, and there was an overall significant 2-fold increase in the area of lung parenchyma affected by these lesions in gp130 F/F :Kras G12D compared with Kras G12D mice ( Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Although collectively these observations imply that STAT3 via IL6 trans-signaling can augment the oncogenic potential of mutant Kras in lung adenocarcinoma, recently it was reported that the lung epithelial-specific inactivation of Stat3 exacerbates Kras G12D -driven lung adenocarcinoma (40). The tumor-suppressive activity of STAT3 was assigned to its ability to sequester cytoplasmic NF-kB and inhibit NF-kB-induced transcription of the proangiogenic chemokine Cxcl1, thus suppressing tumor vascularization and growth.…”
Section: Discussionmentioning
confidence: 99%